Human capital creates insider power - Joan Muysken; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
This paper demonstrates that insiders can erect barriers to entry and skim rents by sinking costs in human capital when labour markets are otherwise perfectly contestable. The sunk costs nature of human capital investments may result from the need to satisfy ever increasing specialised skill requirements in our society. When outsiders can not threat with market entry, insiders invest inefficiently in human capital such that their rent share is maximized. This inefficiency results from the hold-up problem that arises since workers are not residual claimants of the human capital rents. On the other hand, since insiders investments are negatively correlated with the number of workers, this may lead to higher than efficient investments nevertheless. When outsiders have an effective entry threat, insiders are forced to accept higher employment of outsiders and share the reduced rents with them. However, full employment is not necessarily reached and in any case investments are higher and social rent is lower than optimal.
Keywords: J41; J24; 330; Insider-Outsider; Human Capital; Rents; Unemployment; Hold-Up; Insider-Outsider-Modell; Bildungsinvestition; Sunk Costs; Rent Seeking; Unvollständiger Vertrag; Arbeitslosigkeit; Theorie